(untitled) (Lex localis - Journal of Local Self-Government, 2023)
The importance of the application of controlling in public enterprises is highlighted in the study. The aim of the research was aimed at establishing evidence that improvement of management can be achieved through the application of controlling 141 public companies were analyzed in terms of the use of controlling and internal control, that is, about 20% of the mentioned companies whose founders are local self-government units. We found that there are significant differences in terms of established control and it is increasingly in favor of the application of controlling in relation to internal control based on the analyzed five factors: planning, decision-making, business analysis, presentation and reporting. The main conclusion would be that the operations of public companies in the coming period will require an increasing application of controlling in the management system. This was determined by applying the so-called T-test, and the total score, and it refers to all analyzed factors (p=.000) in relation to established controlling and internal control in public companies.